Perhitungan Cadangan Batupasir di Derah Perencanaan Tambang Desa Pegongsoran, Kecamatan Pemalang, Kabupaten Pemalang, Jawa Tengah - Narulita Santi; Wahju K Hidajat; Nur Adillah; Devina Trisnawati; Nurakhmi Qadaryati (MINERAL, 2021)
Indonesia has large number of sandstone reserves throughout the region. One of the potential reserves of Sandstones located in Pegongsoran, Pemalang. The purpose of the study is to know subsurface rock distribution so amount of Sandstones reserves can be determined for mining. The method used is Schlumberger arrays configuration geoelectrical method. Geoelectric measurements carried out at four points, geological mapping also conducted to know geological conditions and surface geomorphology.. From data processing in the field lithology found in the field are volcanic breccia, sandstones, and tuff. To figure out the subsurface conditions and rock layer distribution is performed correlation with three sections A-A’ section consist of GL-04, GL-03, GL-01. The B-B’ section consist of GL-04, GL-02, GL-01 C-C’ section consisting of the geoelectrical points GL-03 and GL-02. Based on volumetric calculation result with model block method using Rockworks software sandstones volume is 2,030,000 m3 while Calculation results using Cross-section method is 1,788,845m3